2020
DOI: 10.1002/zamm.202000087
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamic response of functionally graded material plates using a high‐order implicit algorithm

Abstract: In this paper, the forced nonlinear dynamic behavior of functionally graded material (FGM) plate under external dynamic loads is analyzed by means of a high‐order implicit algorithm. The model is developed using the third‐order shear deformation plate kinematics (TSDT). Unlike previous works, in this contribution, the formulation is written without resorting to any homogenization technique neither rule of mixture nor considering FGM as a laminated composite. To handle integrals in the case of inhomogeneous FGM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In this study, the effect of different boundary conditions has been taken into account as shown in Fig. 5, material properties of FGM plate given in Table 1 are used, and the obtained numerical results are compared with those given in references [18] and [16] in particular case of P-FGM plates. In this part, we examine the influence of the exponent N of the volume fraction for P-FGM and S-FGM.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the effect of different boundary conditions has been taken into account as shown in Fig. 5, material properties of FGM plate given in Table 1 are used, and the obtained numerical results are compared with those given in references [18] and [16] in particular case of P-FGM plates. In this part, we examine the influence of the exponent N of the volume fraction for P-FGM and S-FGM.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The plate is discretized by 5 × 5 elements. The eigen-frequencies have been calculated by the proposed approach for a square P-FGM plate and compared with the results of references [16] and [18] as shown in Table 2. Table 3 presents the calculated eigen-frequencies by the proposed approach for a square S-FGM.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Similarly, the HSDT/TSDT and VKNST kind of modelling approaches are adopted for the computation of dynamic deflections of FGM plates 25 considering the geometrical nonlinearity and porous FG plates. 26,27 A TSDT is utilised 28 to analyse the nonlinear dynamic behaviour of FG plates exposed to external dynamic load. FSDT and VKNST are employed in Nguyen et al 29 and Nazari et al 30 for the computation of nonlinear flexural deflection and/or dynamic responses of the FG plates.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the volume of research publications in this field has experienced exponential growth over the past decades, making FGMs progressively appealing in various engineering fabrication domains. Bourihane et al [7,8] proposed novel finite elements to explore the buckling and vibration behavior of rectangular plates made of Functionally Graded Materials (FGM) using an eigenvalues approach. Sitli and co-workers [9] analyzed the post-buckling behavior of rectangular plates by means of the ANM method.…”
Section: Introductionmentioning
confidence: 99%